Association between Consumption of Cow's Milk and Iron Deficiency Anemia in Children: Are There Roles for Hepcidin-25/Ferroportin? A Case-Control Study. (16th November 2020) - Vehapoglu, Aysel; Ozgurhan, Gamze; Ustabas Kahraman, Feyza; Cakın, Zeynep Ebru; Sumbul, Bilge
Abstract: Systemic iron homeostasis is regulated by the interaction of the peptide hormone, hepcidin and the iron exporter, ferroportin. The objective was to investigate the relationship between the consumption of cow's milk and iron deficiency anemia in children 2–10 years old and its association with the hepcidin-25 and ferroportin concentrations. The study population consisted of 187 prepubescent children of similar ideal body weight (IBW:90–120%); 82 children with iron deficiency anemia (37girls and 45boys; 4.27 ± 0.28 years) and 105 (47girls and 58boys; 4.25 ± 0.34 years) healthy age-sex-matched controls. Serum fasting hepcidin-25/ferroportin concentrations were measured by enzyme immunoassay in all subjects. Mean cow's milk consumption in the anemic group (373 ± 248 mL/d) tended to be higher than that in the control group (320 ± 226 mL/d), but the result was not statistically significant ( p = 0.063).The mean hepcidin-25 level was significantly higher in the anemic group (19.5 ± 18.4 ng/mL) than in the healthy controls (11.0 ± 10.7, p < 0.001). The mean ferroportin level was lower in the anemic group (21.04 ± 5.74 ng/mL) than in the healthy controls (22.68 ± 4.77 ng/ml, p = 0.037). Consuming cow's milk was not associated with IDA in prepubertal children, provided that it was adequately supplemented with iron-enriched foods. We observed a significant increase in hepcidin-25 levels and a decrease in ferroportin levels in children with iron deficiency anemia compared with healthy controls. Children who consumed more cow's milk had higher levels of hepcidin-25. Iron deficiency anemia is not a concern when cow's milk is given to children if the complementary foods are rich in iron.